Copper Incorporation into CdS Thin Films by Ionic Exchange in an Aqueous Solution Process at Room Temperature - E. Flores-García; M. A. Hernández-Landaverde; P. González-García; R. Ramírez-Bon (Journal of Spectroscopy, 2018)
Cadmium sulfide (CdS) thin films were deposited, on glass substrates, at 70°C for 120 min using an ammonium-free chemical bath deposition process. After deposition, the films were placed in a CuCl2 solution for 45, 60, 75, and 90 min, respectively, for their ion exchange, generating CdxCu1-xS films. The obtained films were analyzed by X-ray diffraction, Raman spectroscopy, X-ray wavelength dispersion spectrometry, and scanning electron microscopy. The reference CdS films showed a homogeneous appearance and a yellowish color; elapsing the immersion time, the films changed their color showing a greenish appearance. The X-ray analysis indicated that the CdS films developed a hexagonal structure with preferential orientation along the plane (002). During the ion exchange, a decrease in the intensity of the reflection (002) was observed as well as a slight displacement of this reflection towards higher values of 2θ derived from the substitution of Cd atoms by Cu atoms. The WDS analysis revealed that approximately 10% of the cadmium atoms were replaced by copper ones after 90 min of immersion.